Suggested Scoring Scale for Nurse’s Self as a Role Model in Health Promotion in Primary Health Care Centers - Kamaran A. Faidha, Raad K. Fraj (Pakistan Journal of Medical & Health Sciences, 2023)
Objective(s): To identify Creating new Score for Nurse’s Self as a role Model in Health Promotion. Methodology: A descriptive study design was carried out to measure the Suggested Scoring scale for Nurse’s Self as a role Model in Health Promotion in Primary Health Care Centers and will be used to determine the nurses’ health their perceptions of self as role models for health promotion. The study was started from 8th September 2022 to 16th December 2022. A purposive sample of (127) nurses were selected according to the study that are actual working in Primary Health Care Centers. Validity and reliability of the questionnaire are determined through pilot study. The data were collected by direct interview using specific questionnaire that’s composed of two parts (56) items. Data were analyzed by using (SPSS) package version 22. Descriptive data through determination of: Frequency, percentage, mean of score and standard deviation. Inferential statistical data analysis approach: used by enforcement of the Chi –square test used for determining the association between Socio-demographic characteristics and the Suggested Scoring scale for Nurse’s Self as a role Model in Health Promotion, testing the significant of the contingency coefficient. For study significant P-value (≤ 0.05). Results: The findings indicate that (47.3%) of nurses are the last two age groups (45-49), (≥ 50), while (94.5%)of them are showing educational levels at the diploma. Health Promotion Training shows that about (65.4%), and (66.9%) the studied nurses are assigned exercising. and show a high positive relationship in the response of nurses as a role model in health promotion. Conclusions: The study concluded that a positive relationship between nurses’ health practices and their self-perception as a role model for health promotion will be a highly significant positive relationship between the nurses’ personality as a role model for health promotion and social and demographic characteristics. Recommendations: The present study recommends the need that periodic and regular evaluation of the health promotion program is required at health directorates, health care sectors and primary health care centers for the determination of monitoring its utility. that leads to changing their lifestyle and getting rid of wrong behaviors and habits. Keywords: Scoring scale, self as a model, nurse, health promotion, primary health care.